Hubungan Kepemimpinan Pembelajaran Kepala Sekolah Lingkungan Kerja dan Iklim Sekolah Dengan Sikap Profesional Guru di SMP Negeri Kecamatan Pelaihari Kabupaten Tanah Laut - Shinta Dwi Nanda; Ahmad Suriansyah; Aslamiah Aslamiah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research analyzes the direct and indirect relationship between Principal Learning Leadership, Work Environment, School Climate, and Professional Attitudes of Public Middle School Teachers in Pelaihari District, Tanah Laut Regency. This type of research is quantitative with an explanatory method using a path analysis model to analyze relationship patterns between variables. The research population was 140 teachers from 8 State Middle Schools in Pelaihari District, Tanah Laut Regency, and 104 respondents were taken as research samples using the Probability Simple Random Sampling technique. Data collection uses questionnaire instruments, and data analysis uses descriptive analysis, classical assumption testing, hypothesis testing, and path analysis. The results of the study of the regression coefficient values ​​for the Principal Learning Leadership and Teacher Professional Attitude variables were 0.423, the Work Environment and Teacher Professional Attitude variables were 0.279, the School Climate and Teacher Professional Attitude variables were 0.232, the Principal Leadership and School Climate variables were 0.430, the Work Environment variable and School Climate of 0.515, the Principal Learning Leadership variable through School Climate with Teachers' Professional Attitudes of 0.778 and the Work Environment variable through School Climate with Teachers' Professional Attitudes of 0.805. In conclusion, a partial direct relationship exists between Principal Learning Leadership, Work Environment, and Teacher Professional Attitudes in Public Middle Schools in Pelaihari District, Tanah Laut Regency. There is an indirect relationship between the Principal's Learning Leadership through School Climate and Teachers' Professional Attitudes and the Work Environment through School Climate and Teachers' Professional Attitudes in Public Middle Schools in Pelaihari District, Tanah Laut Regency. Keywords: Principal Learning Leadership, Work Environment, School Climate, Teacher Professional Attitude